Real tax effects and tax perception effects in decisions on asset allocation - Martin Fochmann; Kristina Hemmerich (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
We test the predictions of the theoretical literature initiated by the study of Domar and Musgrave (1944) with a laboratory experiment in which subjects have to decide on the composition of an asset portfolio. Our simple design enables us to distinguish between Real Tax Effects and Perception Effects when a proportional income tax, with and without a full loss offset provision, is introduced. Observed investment behavior is partially inconsistent with the theoretical predictions if we do not control for the Perception Effects. However, if we consider these effects, we find support for the theory. The isolated Perception Effects can explain the unexpected behavior observed in previous studies and has both scientific and political implications.
Keywords: C91; D14; H24; 330; Taxation; Domar-Musgrave Effect; Tax Perception; Risk Taking Behavior; Portfolio Choice; Behavioral Taxation